Trade Credit: Theories and Evidence - Petersen, Mitchell A.; Rajan, Raghuram G. (Review of Financial Studies, 1997)
In addition to borrowing from financial institutions, firms may be financed by their suppliers. Although there are many theories explaining why non-financial firms lend money, there are few comprehensive empirical tests of these theories. This paper attempts to fill the gap. We focus on a sample of small firms whose access to capital markets may be limited. We find evidence that firms use trade credit relatively more when credit from financial institutions is not available. Thus while short term trade credit may be routinely used to minimize transactions costs, medium term borrowing against trade credit is a form of financing of last resort. Suppliers lend to firms no one else lends to because they may have a comparative advantage in getting information about buyers cheaply, they have a better ability to liquidate goods, and they have a greater implicit equity stake in the firm's long term survival. We find some evidence consistent with the use of trade credit as a means of price discrimination. Finally, we find that firms with better access to credit from financial institutions offer more trade credit. This suggests that firms may intermediate between institutional creditors and other firms who have limited access to financial institutions.